2022
DOI: 10.1038/s41928-022-00866-z
|View full text |Cite|
|
Sign up to set email alerts
|

An anomalous Hall effect in altermagnetic ruthenium dioxide

Abstract: Anomalous Hall effect is a time-reversal symmetry breaking electronic response discovered in ferromagnets in the 19th century and continuing to play a key role in modern fields of physics and nanoelectronics. In contrast, the antiparallel magnetic order on common rutile crystals served as a classic example which kept compensated magnets for nearly a century outside the focus of the magneto-electronic research. Breaking with this traditional perception, the antiparallel magnetic order on the rutile crystal of R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
63
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 185 publications
(69 citation statements)
references
References 48 publications
6
63
0
Order By: Relevance
“…Three mechanisms cause the conventional AHE: intrinsic contribution by the Berry phase and extrinsic contributions by skew scattering and side jump. [40,41] In this study, such an AHE in the heterostructure system occurs owing to the interaction between the spin current (SHE in HM) and the magnetic structure (magnetic insulator, in this case, AFMI). Recently, it has been reported that an AFM topological spin texture emerges around the phase-transition temperature of Pt/α-Fe 2 O 3 heterostructures.…”
Section: Resultsmentioning
confidence: 94%
“…Three mechanisms cause the conventional AHE: intrinsic contribution by the Berry phase and extrinsic contributions by skew scattering and side jump. [40,41] In this study, such an AHE in the heterostructure system occurs owing to the interaction between the spin current (SHE in HM) and the magnetic structure (magnetic insulator, in this case, AFMI). Recently, it has been reported that an AFM topological spin texture emerges around the phase-transition temperature of Pt/α-Fe 2 O 3 heterostructures.…”
Section: Resultsmentioning
confidence: 94%
“…Three mechanisms cause the conventional AHE: intrinsic contribution by the Berry phase and extrinsic contributions by skew scattering and side jump. [ 40,41 ] In this study, such an AHE in the heterostructure system occurs owing to the interaction between the spin current (SHE in HM) and the magnetic structure (magnetic insulator, in this case, AFMI). Recently, it has been reported that an AFM topological spin texture emerges around the phase‐transition temperature of Pt/ α ‐Fe 2 O 3 heterostructures.…”
Section: Resultsmentioning
confidence: 98%
“…[15][16][17][18] The crystal structure and Néel vector of AFM provide a unique opportunity for tailoring the THz emission. [19,20] Recently, the altermagnetic materials with collinear compensated magnetic order and crystal rotation symmetry have been demonstrated to show strong time-reversal (T) symmetrybreaking responses, [21][22][23][24][25][26] such as the anomalous Hall effect [27][28][29] and the non-trivial spin current generation, [30][31][32][33][34] which are ascribed to the nonrelativistic altermagnetic spin splitting effect (ASSE). As a typical representative of altermagnetisms, the rutile RuO 2 possesses large spin splitting strength (≈1.4 eV [21] ), high conductivity (≈35 μΩcm [35] ) and high Néel temperature (above 300 K [36,37] ), attracting continuous attention for the application in spintronic devices.…”
Section: Introductionmentioning
confidence: 99%